Kemampuan Mengikat Air oleh Tanah Pasir yang Diperlakukan dengan Tepung Rumput Laut Gracilaria verrucosa - Sinulingga, Maranatha; Darmanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2007)
Sand is media plant which was ability fasten the water absorb of very low. Sea weed of Gracilaria verrucosa pregnant of gel able to fasten water. This research aim to know of ability fasten waterby mixed sand with Gracilaria verrucosa flour at some comparations. Research use random device complete with 4 treatment, every treatment by 5 restating. Result of research indicate that ever greaterly of comparison of grass flour go out to sea to sand, hence juicy progressively able to be bound by sands.